2009
DOI: 10.1287/orsc.1080.0388
|View full text |Cite
|
Sign up to set email alerts
|

Value of Strong Ties to Disconnected Others: Examining Knowledge Creation in Biomedicine

Abstract: K nowledge creation requires the combination and exchange of diverse and overlapping knowledge inputs as individuals interact with exchange partners to create new knowledge. In this study, we examine knowledge creation among university research scientists as a function of their professional (ego) networks-those others with whom they collaborate for the purpose of creating new knowledge. We propose that knowledge creation relies, in part, on two attributes of a researcher's professional network structure-averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
222
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(241 citation statements)
references
References 80 publications
(110 reference statements)
9
222
0
3
Order By: Relevance
“…Previous research has also found that weak tie sources transfer and secure codified knowledge efficiently and easily (Hansen, 1999). For example, a knowledge worker that has mostly weak tie sources with direct exchange partners would have few obligations to those partners (McFadyen, Semadeni, & Cannella, 2009). Furthermore, Perry-Smith (2006) finds a positive link between the number of weak tie acquaintances in scientists' networks and creativity.…”
Section: Antecedents Of Breadth Of Absorptive Capacitymentioning
confidence: 98%
See 1 more Smart Citation
“…Previous research has also found that weak tie sources transfer and secure codified knowledge efficiently and easily (Hansen, 1999). For example, a knowledge worker that has mostly weak tie sources with direct exchange partners would have few obligations to those partners (McFadyen, Semadeni, & Cannella, 2009). Furthermore, Perry-Smith (2006) finds a positive link between the number of weak tie acquaintances in scientists' networks and creativity.…”
Section: Antecedents Of Breadth Of Absorptive Capacitymentioning
confidence: 98%
“…Strong tie sources contain much overlapping, but less diverse, knowledge (McFadyen, Semadeni, & Cannella, 2009). Research has established several benefits of strong tie sources relevant to knowledge transfer, acquisition, and creation.…”
Section: Antecedents Of Depth Of Absorptive Capacitymentioning
confidence: 99%
“…Diversity facilitates the integration of different specialties, it contributes to the successful development of a project and shortens the development time of a new product (Cummings, 2004;Eisenhardt & Tabrizi, 1995;Griffin & Hauser, 1992;Pinto, Pinto, & Prescott, 1993). For this reason, academicians with different abilities, skills, experience and knowledge should work together in a cohesive team (McFadyen, Semadeni, & Cannella, 2009). It is believed that the performance will increase through the internal and external sharing of information within the groups with diversities (Monge, Rothman, Eisenberg, Miller, & Kirste, 1985).…”
Section: Cultural Diversity-performance Relationshipmentioning
confidence: 99%
“…This is because the prior alliance experience and common partners provide the firms with easy access to information about potential partners and give them some control over the partners' opportunistic behaviors through emotional intimacy and reputational referrals (Shipilov, Rowley, & Aharonson, 2006;Uzzi, 1996). Accordingly, several prior studies have found that two firms that have prior partnerships or many common partners are likely to form a new alliance (Gulati, 1995;Uzzi, 1996) and that such alliances tend to produce strong gains (Capaldo, 2007;McFadyen, Semadeni, & Cannella, 2009;Rowley, Behrens, & Krackhardt, 2000).…”
Section: Introductionmentioning
confidence: 99%